Pengaruh Current Ratio, Return on Equity, Debt to Equity Ratio dan Price to Book Value terhadap Return Saham (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Stock return, which represents the level of profit anticipated by investors in the capital market, is greatly influenced by the company's financial performance. A stronger financial performance typically correlates with higher potential stock returns. Consequently, investors necessitate a thorough evaluation of the financial performance of prospective investment targets. Utilizing financial ratio analysis proves instrumental in assessing a company's financial strengths and weaknesses, thereby facilitating informed investment decisions. This research objectives to investigate the influence of various financial metrics, including return on equity, price to book value, debt to equity ratio, also current ratio on stock returns, both individually and collectively. Employing a quantitative research approach, the study encompasses all shares of companies within the consumer non-cyclicals sector listed on the main board of the IDX from 2018 to 2022, with 39 companies selected as samples by applying purposive sampling. Descriptive statistical tests, also multiple linear regression analysis, were utilized to evaluate the relation between these metrics and stock returns. The findings suggest that while the current ratio may have a positive but insubstantial impact on stock returns individually, DER, ROE, as well as PBV exhibit a substantial positive influence on stock returns. Moreover, when considered collectively, these variables collectively demonstrate a substantial and substantial impact on stock returns.